Understanding how traumatic brain injury-related changes in fluid biomarkers affect quality of life outcomes in veterans: a prospective observational trial protocol (UNTANGLE) - Antonio Belli; Richard J Blanch; Christel McMullan; Rachel Upthegrove; Zubair Ahmed; Renata S M Gomes; Youstina Metry (BMJ Open, 2024)
Introduction Traumatic brain injury (TBI) is a major cause of disability, with annual global incidence estimated as 69 million people. Survivors can experience long-term visual changes, altered mental state, neurological deficits and long-term effects that may be associated with mental illness. TBI is prevalent in military personnel due to gunshot wounds, and blast injury. This study aims to evaluate the relationship between evolving visual, biochemical and mental health changes in both military veterans and civilians, suffering from TBI, and detect preliminary indicators of prognosis for TBI recovery, and quality-of-life outcomes.Methods and analysis UNTANGLE is a 24-month prospective observational pilot study recruiting three patient groups: civilians with acute moderate-severe TBI, military veterans with diagnosis of a previous TBI and a control group of civilians or veterans with no history of a previous TBI. Patients will undergo visual, biochemical and mental health assessments, as well as patient-reported quality of life outcome measures over the course of a 1-year follow-up period.Ethics and dissemination Ethical approval has been obtained from the Health Research Authority and Health and Care Research Wales with a REC reference number of 23/NW/0203. The results of the study will be presented at scientific meetings and published in peer-reviewed journals, including both civilian and military-related publications. We will also present our findings at national and international meetings of learnt neuroscience and neuropsychiatry and military societies. We anticipate that our pilot study will inform a larger study on the long-term outcomes of TBI and quality of life, specific to military veterans, such that potential interventions may be accessed as quickly as possible.Trial registration number ISRCTN13276511.